Didactics of Literature: Didactic Techniques for the Aesthetic Modelling Strategy - Altamirano Flores, Federico (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In the context of the theory of literary contagion, the present article aims to propose techniques to put into practice the didactic strategy of aesthetic modeling. From the observation of the literature classes of writers such as Jorge Luis Borges, Vladimir Nabokov and Julio Cortázar, and from the reflection on the testimonies, opinions and interviews of Daniel Pennac and Luis Landero, we propose three didactic techniques that may serve to awaken the passion for literature in students. These techniques are: expres- sive reading, commented reading and oral narration, conceived as discursive activities that convey the teacher’s emotion and literary experience in the classroom.